Produksi Asam Levulinat dari Inulin Umbi Dahlia (Dahlia sp. L) Menggunakan Katalis Asam Klorida - Murwindra, Rosa; Linggawati, Amilia; Yanti, Pepi Helza; Awaluddin, Amir; ', Saryono (Jurnal Natur Indonesia, 2016)
Dahlia is a floriculture plant with tuber that rich of inulin. Inulin is soluble in hot water and it will settle on cool temperature in alcohol. Extraction of result from 100 g dahlia tuber taken from Bukittinggi, West Sumatra is 4% inulin (w/w dahlia tuber). Inulin flour produced is white gray. Qualitative tests with Seliwanoff and Nelson-Somogyi methods shows that inulin positive contained of fructose and reducing sugar. Extracted result of inulin can be converted into levulinic acid using acid catalyst at high temperature. In this experiment, production of levulinic acid will bundle with variate temperature, reaction time and catalyst concentration of hydrochloride acid. The reaction of inulin convertion was done in ampul that burned in oven. Conversion result of 5% inulin to be levulinic acid on heating 150 o C hydrochloride acid concentration 0,1 M about 25 minutes was 12,33% (w/w inulin). On heating 170 o C hydrochloride acid concentration 0,1 M about 15 minutes is 26,25% (w/w inulin), while on heating 150 o C hydrochloride acid concentration 1 M about 15 minutes is 32,28% (w/w inulin). Experiment result showed that concentration of glucose, levulinic acid and formiat acid increase with increasing in reaction reaction temperature while fructose concentration decrease from 55,14 mg/mL to be 0,12 mg/mL. The longer time reaction and the higher concentration of catalyst hydrochloride acid, the lower concentration of glucose and fructose and the larger concentration of levulinic acid and formic acid.